Strategi Produser Dalam Memproduksi Program Televisi Studi Kasus : Proses Produksi Program Acara Ayo Hidup Sehat Di Tvone - Defhany Defhany; Annita Zarfinal (LPPM Universitas Dharma Andalas, 2022)
This research describes how the producer determining the theme of episode on the “Ayo Hidup Sehat” program, The program are aired every week. This research aims to explains the creative strategies, and obstacles that the producer faces in producing the